Multiplex vs. singleplex assay for the simultaneous identification of the three components of avian malaria vector-borne disease by DNA metabarcoding - Eduard Mas-Carrió; Judith Schneider; Victor Othenin-Girard; Romain Pigeault; Pierre Taberlet; Philippe Christe; Olivier Glaizot; Luca Fumagalli (PeerJ)
Accurate detection and identification of vector-host-parasite systems are key to understanding their evolutionary dynamics and to design effective disease prevention strategies. Traditionally, microscopical and serological techniques were employed to analyse arthropod blood meals for host/parasite detection, but these were limited in taxonomic resolution and only to pre-selected taxa. In recent years, molecular techniques have emerged as a promising alternative, offering enhanced resolution and taxonomic range. While singleplex polymerase chain reaction (PCR) assays were used at first to identify host, vector and parasite components in separate reactions, today multiple primer pairs can be combined in a single reaction, i.e., multiplex, offering substantial time and cost savings. Nonetheless, despite the potential benefits of multiplex PCR, studies quantifying its efficacy compared to singleplex reactions are scarce. In this study, we used partially digested mosquito blood meals within an avian malaria framework to jointly identify the host, vector and parasite using multiplex DNA metabarcoding, and to compare it with separate singleplex PCRs. We aimed to compare the detection probabilities and taxonomic assignments between both approaches. We found both to have similar performances in terms of detection for the host and the vector, but singleplex clearly outperformed multiplex for the parasite component. We suggest adjusting the relative concentrations of the PCR primers used in the multiplex assay could increase the efficiency of multiplex in detecting all the components of the studied multi-species system. Overall, the results show that multiplex DNA metabarcoding can be an effective approach that could be applied to any vector-borne interaction involving blood-feeding arthropods. Our insights from this proof-of-concept study will help improve laboratory procedures for accurate and cost-efficient medical diagnosis of vector-borne diseases, the spread of which is globally exacerbated by current climate change.